Aetiology and management of epistaxis at TU Teaching Hospital - Adhikari, P; Thapa, NM; Sinha, BK (Journal of Institute of Medicine Nepal, 2007)
Background: Epistaxis is a common condition, aswell as a frequent otolaryngologic emergency. Up to 60% of people experiencing one episode in their lifetime and 6% seeking medical attention. Methods: A retrospective study of records of 93 patients admitted in the department of ENT-Head and Neck Surgery of TU Teaching Hospital for the management of epistaxis in betweenMarch 2005 and February 2006. Results: The incidence of epistaxis was found to be in 6.0% of all the ENT patients admitted in the department in this time period. Themost common cause / risk factors were hypertension followed by deviated nasal septum. In 24.7% of cases no cause could be found and was labeled as idiopathic. Regarding treatment, 9.7%treatedwithChemical cautery, 34.4%anterior nasal packing, 25.8%posterior nasal packing and 2.2% required arterial ligation to control their epistaxis. Conclusion: Our study shows that epistaxis is also a common emergency. Etiology could be found nearly 75%of cases only which could be preventable.Anterior Nasal Packing was themost common treatment. We should manage a case of epistaxis in an orderly manner. KeyWords: Epistaxis, anterior nasal packing, posterior nasal packing; arterial ligation. The full text of this paper is available at Journal of Institute of Medicine website